Creating a biodiversity science community: Experiences from a European Network of Knowledge. Issue 54 (December 2015) - Carmen, Esther; Nesshöver, Carsten; Saarikoski, Heli; Vandewalle, Marie; Watt, Allan; Wittmer, Heidi; Young, Juliette
Highlights: Evaluation of an initiative to bring together knowledge to inform decision making. Identifies challenges and tangible options for improvement. Benefits from broadening and organising knowledge communities are recognised. Coordinated action, new methods and behaviour change are required. Facilitating knowledge exchange can build capacity to bring knowledge together. Abstract: As biodiversity continues to decline despite our increased knowledge of the drivers and consequences of biodiversity loss, much of the current focus is on strengthening interfaces between biodiversity knowledge and policy-making. While many of the challenges associated with science–policy interfaces are well known, what is less well studied is the more specific issue of how to integrate the broad range of knowledge relating to complex issues such as biodiversity and ecosystem services, to inform decision-making at regional and global scales. Based on a formative evaluation of the development of a European Network of Knowledge on biodiversity and ecosystem services, we identify key themes to build a broad biodiversity science community capable of developing integrated knowledge to inform decision-making. Based on these findings we outline future steps for the successful integration of knowledge in decision-making at the European, and also the global scale, in particular the Intergovernmental Panel on Biodiversity and Ecosystem Services (IPBES).